Pins and posters: paradigms for content publication on situated displays - José, Rui (2013)
Public display systems are still far from being a communication medium that people can appropriate to serve diverse communication goals. Moving towards open displays will require new publication paradigms that can overcome the challenges of meaningful engagement and enable users to fully understand and control the entire publication process. In this paper, we report on the study of two novel and complimentary communication paradigms for public displays inspired by the metaphors of pin badges and posters. The study is grounded on a 6 month deployment of Instant Places across 10 displays in diverse urban locations. We have collected user and system data regarding the emerging practices around these publication paradigms. The findings from this study constitute a novel contribution towards understanding the elements that may drive user-generated content in networks of urban displays, informing the design of new tools and procedures for situated publication in public displays.